2011
DOI: 10.1097/jto.0b013e31820b86cb
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Fine Needle Aspiration Cytology in the Pathological Typing of Non-small Cell Lung Cancer

Abstract: FNAC in expert hands is fairly accurate for typing NSCLC and can be regarded as an acceptable procedure for diagnostic and medical treatment planning purposes in most NSCLC cases, especially when more invasive approaches are unfeasible. In poorly differentiated and doubtful cases, the use of ancillary techniques, such as immunocytochemistry, may be required to improve the diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 27 publications
7
86
0
Order By: Relevance
“…A more recent study examined the accuracy of fine-needle aspirate cytology (FNAC) specimens in differentiating squamous from non-squamous NSCLC [33]. The authors retrospectively reviewed 474 patients who had NSCLC diagnosed by FNAC and identified 186 who had tissue retrieved by other means and noted good agreement between cytological and histological diagnoses (k50.755).…”
Section: Lung Cancer Dp Steinfort Et Almentioning
confidence: 99%
“…A more recent study examined the accuracy of fine-needle aspirate cytology (FNAC) specimens in differentiating squamous from non-squamous NSCLC [33]. The authors retrospectively reviewed 474 patients who had NSCLC diagnosed by FNAC and identified 186 who had tissue retrieved by other means and noted good agreement between cytological and histological diagnoses (k50.755).…”
Section: Lung Cancer Dp Steinfort Et Almentioning
confidence: 99%
“…However the quantities of pathological materials obtained by biopsy are not always sufficient for subtyping or genotyping; thus in addition to histological specimens, cytological specimens should be used for subtyping, as this might expand treatment choices [14,15]. Nizzoli et al [16] investigated the accuracy of fine needle aspiration cytology (FNAC) in NSCLC typing in comparison to histology. In their study, the cytological and histological typing was concordant in 137 of 156 (88%) cases (K=0.755; p<0.001), and the positive predictive value of FNAC in predicting the type of NSCLC was 92% for adenocarcinoma and 82% for squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nizzoli R et al [11] analyzed 474 primary NSCLCs cytologically with comparison of 186 cases with parallel endoscopic biopsies or surgical material and concluded that FNAC is fairly accurate for subtyping of NSCLC and in doubtful cases , immunohistochemistry can be added to improve diagnostic yield. In this study, the authors analyzed adenocarcinoma and squamous cell carcinoma based on background, architecture and cytoplasmic and nuclear characteristics as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…(refer tables 1&2) Non small cell carcinomas were further subtyped into adenocarcinoma(ADC) and squamous cell carcinoma(SCC) based on following features: background, architecture, cytoplasmic and nuclear details and presence of nucleoli. [11,12] (Table 3). Based on these features, 12 and 5 cases were subtyped into adenocarcinoma(figure5a,b,c) and squamous cell carcinoma(figure 6)respectively.…”
Section: Introductionmentioning
confidence: 99%